UJI PENDAHULUAN PEMANFAATAN GAS KARBONDIOKSIDA UNTUK SIMULASI PENGOLAHAN LIMBAH CAIR YANG MENGANDUNG LOGAM BERAT TIMAH mTAM - Ardeniswan Ardeniswan (Research Center for Chemistry - LIPI, 2012)
Wastewater used in this experiment is an artificial wastewater containing lead. First, lead was precipitated with 0.1 M NaOH at pH 9 as hydroxide compound [Pb(OH)J. After Pb(OH)2 precipitated, CO2gas with a concentration of 16% isflowed as much as 120 mL with aflow rate of 120mLimin, where the lead remaining will settle to form lead carbonate (PbCOJ. A part of the precipitate was directly leached without any process of stabilization/ solidification and another part was leached after stabilization/solidification using Portland cement. Subsequent of precipitation that above were added of extraction solution with pH is 2.85 ± 0.05 in the ratio 1: 20. Leaching or TCLP test (Toxicity Characteristic leachate procedure) was conducted using a Rotary Agitator with a rotation speed of 30±2 rpmfor 18±2 hours. The TCLP test results showed that each compound PbC03 and Pb(OH)2 by weighing 1.5g without any solidification process were 91.34 ± 8.74 mg/L and 45.6 :I:0.14 mg/L respectively. These values were exceeds the required quality standardfor TCLP. While the compounds of PbC03 and Pb(OH)2 respectively with a weight of 1.5 g were carried out the stabilization / solidification withPortland cement in the ratio of 1:1:1 (cement: sand: solid waste), apparently both of lead ions fromPbC03 andPb(OH)2 were not leached.Keyword : Carbon dioxide, wastewater, Pb+1, stabilisationlsolidification, TCLP Test